HUBUNGAN NILAI STATUS GIZI DENGAN NYERI DISMENORE PRIMER PADA REMAJA PUTRI SMA NEGERI 1 PASIRIAN LUMAJANG - Wulandari, Veronica Genius; Ermawati, Iit; Sary, Yessy Nur Endah (NHM PRESS, 2023)
Primary dysmenorrhea is spasmodic and limited pain felt in the lower abdomen and can radiate to the back and inner thighs such as squeezing, throbbing headache, nausea, vomiting, lower back pain and even fainting. Factors that can trigger and exacerbate primary dysmenorrhea are family history of dysmenorrhea, history of exercise habits and nutritional status (BMI) in the underweight and overweight categories which have an impact on reproductive function in adolescents. The purpose of this study was to analyze the correlation between nutritional status and primary dysmenorrhea pain in class X students at SMA Negeri 01 Pasirian Lumajang. The research design used descriptive quantitative research with a cross-sectional approach. The population in this study were all 210 class X students with a total sample of 60 students using the simple random sampling method by collecting data, namely anthropometric measurements. The research test used Spearmen's Rank to determine whether there was a correlation between the value of nutritional status and primary dysmenorrhea. The Rho value with the help of the SPSS 26 analysis software analysis with Spearmen Rank shows the results Sig(2-tailed) = 0.039 so that which means that the Sig(2-tailed) value is less than vulnerable 0.05 or 0.01, then the relationship is said to be significant. The correlation coefficient is 0.765, the correlation strength value is 0.76-0.99, and the correlation is very strong because the correlation value is close to -1 or + 1, the correlation is getting stronger, which means that H0 is rejected or H1 is accepted. It can be interpreted that there is a relationship between the value of nutritional status and primary dysmenorrhea pain at SMA Negeri 01 Pasirian Lumajang.